Removal of DB71 Dye from Water Using Shrimp-shell Chitosan - Van Son, Tran; Thanh Ha, Nguyen; Thanh Binh, Dong (VNU Journal of Science: Earth and Environmental Sciences, 2023)
Chitosan is a natural-derived polymer which has been used for water treatment due to its biodegradability. In this study, chitosan adsorbent was successfully fabricated from shrimp crust. The chitosan adsorbents were characterized using FTIR, SEM, and Zeta potential analysis. The experimental results indicated that fabricated chitosan in this study has similar properties to standard chitosan from Sigma-Aldrich which contains functional groups such as -OH, -CH, C-O-C, saccharide rings and amide groups I, II, III. Furthermore, the surface morphology of the adsorbent is moderately flat and the pH PZC was 7.2. Chitosan in flake forms could adsorb DB71 dye in water with a concentration of 35 ppm at the efficiency of 100%. The optimal conditions for the dye removal were at  0.2 g/L of concentration and contact time of 60 minutes. The dye is well adsorbed by chitosan in acidic environment with optimal pH of 3. The main mechanisms of dye adsorption onto the chitosan adsorbent maybe ion exchange or complexation.